Grid application / Tan Kien Peng - Tan, Kien Peng (2005)
After Grid computing introduced since 1995, many research done for the Grid computing. Most of the grid computing research project are focusing on the science. Some vendors such as IBM, Oracle and others start introduce Grid computing to the industry. Basically, my project focused on the data grid. A web based FSKTM data portal is developed for users to access into the data portal. The lecturers and students can gather the resources from the databases. They can find out the related resources from distributed and multiple databases which are located in the heterogeneous platforms. Besides that, lecturers can analyze data from the databases. They can analyze student's result and distribution of students. The middleware that used to develop FSKTM data portal is OGSI.NET. It supports the development of web services. Visual C# is used to develop this project. Besides that, I hope this project to help lecturers and students in gathering related resources in the databases.